Pathogenicity of Fusarium graminearum and F. meridionale on soybean pod blight and trichothecene accumulation - Chiotta, María Laura (2016)
Soybean (Glycine max) is the most important crop in Argentina. At present Fusarium graminearum is recognized as a primary pathogen of soybean in several countries in the Americas, mainly causing seed and root rot and pre‐ and post‐emergence damping off. However, no information about infections at later growth stages of soybean development and pathogenicity of F. graminearum species complex is available. Therefore, the objectives of this study were to compare the pathogenicity of F. graminearum and F. meridionale isolates towards soybean under field conditions and to evaluate the degree of pathogenicity and trichothecene production of these two phylogenetic species that express different chemotypes. Six isolates of F. graminearum and F. meridionale were evaluated during 2012/13 and 2013/14 soybean growing seasons for pod blight severity, percentage of seed infected in pods and kernel weight reduction. The results showed a higher aggressiveness of both F. graminearum and F. meridionale species during the 2013/14 season. However, the differences in pathogenicity observed between the seasons were not reflected in a distinct trichothecene concentration in soybean seeds at maturity. Fusarium meridionale isolates showed similar pathogenicity to F. graminearum isolates but they were not able to produce this toxin in planta during the two field trials.